Structure of the NheA component of the Nhe toxin from Bacillus cereus: implications for function. - Magdah Ganash; Danh Phung; Svetlana E Sedelnikova; Toril Lindbäck; Per Einar Granum; Peter J Artymiuk (PLoS ONE)
The structure of NheA, a component of the Bacillus cereus Nhe tripartite toxin, has been solved at 2.05 Å resolution using selenomethionine multiple-wavelength anomalous dispersion (MAD). The structure shows it to have a fold that is similar to the Bacillus cereus Hbl-B and E. coli ClyA toxins, and it is therefore a member of the ClyA superfamily of α-helical pore forming toxins (α-PFTs), although its head domain is significantly enlarged compared with those of ClyA or Hbl-B. The hydrophobic β-hairpin structure that is a characteristic of these toxins is replaced by an amphipathic β-hairpin connected to the main structure via a β-latch that is reminiscent of a similar structure in the β-PFT Staphylococcus aureus α-hemolysin. Taken together these results suggest that, although it is a member of an archetypal α-PFT family of toxins, NheA may be capable of forming a β rather than an α pore.